ENVIRONMENTAL DEGRADATION IN THE NIGER DELTA AN ETHICAL APPRAISAL - Finomo Julia, Awajiusuk (Asian Horizons, 2012)
From the beginning, humans have consistently interacted with the environment. Available evidence suggests that from the earliest times, humans’ relationship with the environment was perceived as that of a superior and a subordinate, with man regarding nature as the super-ordinate reality and themselves as the subordinate. However, rapid advancements in science and technology have brought about radical changes in human’s attitude towards nature. Equipped with sophisticated and more efficient tools, and propelled by a radically different intellectual orientation and religious outlook, humankind’s attitude and relationship with nature began to change. Nature became depersonalized, and the earth no longer considered as something organic, but as dead matter that could be taken apart, studied and ultimately understood and synthesized. This radical change of attitude, which some environmentalists choose to refer to as the “arrogance of humanism” has culminated in the ruthless exploitation, depletion and degradation of the environment. Capitalist economics now assert that the earth is a mere resource that can be tapped, managed, developed and distributed. This nonchalant attitude has led humans to exploiting the resources of the earth without caution, neither are they perturbed about the damage being inflicted on the earth.